Typology Study of Ulul Albab as Ideal Human Character in Islam (Psychological Analysis of Human Thinking Activities in the Qur'an) - Furqan, Muhammad; Hajar, Ibnoel; Z., Marwan; Mahmud, Salami (Universitas Islam Negeri Raden Intan Lampung, 2023)
The study of the typology of ulul albab as an ideal human character in Islam is an important aspect in understanding the concept of spirituality and wisdom in religion. In the Qur'an, ulul albab is described as an individual who reaches a level of perfection in his thinking activities, reflected in the depth of his spirituality and wisdom in living life. By considering a psychological perspective on human thinking activities, this study aims to explore the meaning and implications of the ulul albab typology in the context of human life. Through a descriptive qualitative approach and library research, data was collected from various relevant reading sources. The data analysis process uses a flowing data analysis method, including reading, recording, processing and concluding. The findings show that thinking involves the entire human personality, explained in the Qur'an. The integration of the Ulul Albab typology in Islam highlights the importance of thinking activities as a basis for devotion and wisdom. In the modern era, Al-Qur'an-based education emphasizing the development of the Ulul Albab character through thinking activities can be a relevant solution in forming an intelligent and devout generation. This study contributes to enriching understanding of thinking activities within a psychological framework and Islamic teachings.